2022
DOI: 10.1111/cts.13348
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of drug–drug interaction potential with EDP‐305, a farnesoid X receptor agonist, in healthy subjects

Abstract: EDP‐305 is a farnesoid X receptor (FXR) agonist that selectively activates FXR and is a potential treatment for patients with nonalcoholic steatohepatitis (NASH) with liver fibrosis. Results from preclinical studies indicate that CYP3A4 is the primary enzyme involved in EDP‐305 metabolism and that EDP‐305 has low potential to inhibit or induce cytochrome (CYP) isoenzymes and drug transporters. Four studies were conducted in healthy volunteers to evaluate the drug–drug interaction (DDI) potential of EDP‐305 co‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
2
1
0
Order By: Relevance
“…PD effects indicative of FXR activation have shown a more pronounced effect in patients with presumptive NAFLD and NASH when compared with healthy subjects. 25,31,[37][38][39] In this study with EDP-297, target engagement was confirmed by decreases in C4 levels and increases in FGF-19 levels during 14 days of treatment. Increases in liver enzyme levels have been observed with other FXR agonists.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…PD effects indicative of FXR activation have shown a more pronounced effect in patients with presumptive NAFLD and NASH when compared with healthy subjects. 25,31,[37][38][39] In this study with EDP-297, target engagement was confirmed by decreases in C4 levels and increases in FGF-19 levels during 14 days of treatment. Increases in liver enzyme levels have been observed with other FXR agonists.…”
Section: Discussionsupporting
confidence: 64%
“…Consistent with FXR target engagement, FGF‐19 levels increased and C4 levels decreased from baseline during a 12‐week study with EDP‐305, 37 as well as in a 24‐week study with cilofexor, 25 which is similar to effects observed with other FXR agonists. PD effects indicative of FXR activation have shown a more pronounced effect in patients with presumptive NAFLD and NASH when compared with healthy subjects 25,31,37–39 . In this study with EDP‐297, target engagement was confirmed by decreases in C4 levels and increases in FGF‐19 levels during 14 days of treatment.…”
Section: Discussionsupporting
confidence: 59%
“…Farnesoid-X-receptor (FXR) and the G protein-coupled bile acid receptors are two widely studied bile acids regulating receptors, which play important roles in lipid and glucose metabolism, inflammation, fibrosis, and immune responses. Many FXR ligands have been investigated in clinical trials for NASH and liver fibrosis treatments, such as EDP-305[ 41 , 42 ], cilofexor[ 43 , 44 ], and MET409[ 45 , 46 ]. Hepatic concentrations of conjugated 12α-hydroxylated bile acids, such as taurodeoxycholate and glycodeoxycholate, were significantly increased in patients with NASH and mouse liver fibrosis models[ 47 ].…”
Section: Signaling Pathways and Molecular Targets For Liver Fibrosis ...mentioning
confidence: 99%